Gender role reversal and the violated lesbian body : toward a feminist hermeneutic of lesbian sadomasochism - Hornsby, Teresa J. (Lesbian sex scandals : sexual practices, identities, and politics)
"Fonds Suzan Daniel (FSD) Teresa J. Hornsby"